Characterization of indoor aerosol temporal variations for the real-time management of indoor air quality. (October 2015) - Ciuzas, Darius; Prasauskas, Tadas; Krugly, Edvinas; Sidaraviciute, Ruta; Jurelionis, Andrius; Seduikyte, Lina; Kauneliene, Violeta; Wierzbicka, Aneta; Martuzevicius, Dainius
Abstract: The study presents the characterization of dynamic patterns of indoor particulate matter (PM) during various pollution episodes for real-time IAQ management. The variation of PM concentrations was assessed for 20 indoor activities, including cooking related sources, other thermal sources, personal care and household products. The pollution episodes were modelled in full-scale test chamber representing a standard usual living room with the forced ventilation of 0.5 h −1 . In most of the pollution episodes, the maximum concentration of particles in exhaust air was reached within a few minutes. The most rapid increase in particle concentration was during thermal source episodes such as candle, cigarette, incense stick burning and cooking related sources, while the slowest decay of concentrations was associated with sources, emitting ultrafine particle precursors, such as furniture polisher spraying, floor wet mopping with detergent etc. Placement of the particle sensors in the ventilation exhaust vs. in the centre of the ceiling yielded comparable results for both measured maximum concentrations and temporal variations, indicating that both locations were suitable for the placement of sensors for the management of IAQ. The obtained data provides information that may be utilized considering measurements of aerosol particles as indicators for the real-time management of IAQ. Highlights: Temporal variation of indoor PM has been quantitatively characterized. Database for dynamic control of IAQ based on PM sensors has been created. Removal of UFPs from indoor air by ventilation is complicated. Centre of ceiling and exhaust ventilation serve as adequate sites for PM sensors.